2021
DOI: 10.2147/ijgm.s302916
|View full text |Cite
|
Sign up to set email alerts
|

Potential Genes and Mechanisms Linking Intracerebral Hemorrhage and Depression: A Bioinformatics-Based Study

Abstract: Purpose The purpose of this study was to investigate the potential pathogenic mechanisms of post-intracerebral hemorrhage depression. Methods Profiles of gene expression in brain tissue of patients with intracerebral hemorrhage (ICH) or depression were downloaded from the Gene Expression Omnibus (GEO) database. We analyzed differentially expressed genes (DEGs) for the two diseases separately. With these DEGs, we conducted an enrichment analysis based on Gene Ontology (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Depression after ICH significantly affects prognosis, and Jun is the central gene in the post-ICH depression gene regulatory network [ 34 ]. Jun-related products are also involved in inflammation, stress response [ 35 ] and the development of central nervous system diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Depression after ICH significantly affects prognosis, and Jun is the central gene in the post-ICH depression gene regulatory network [ 34 ]. Jun-related products are also involved in inflammation, stress response [ 35 ] and the development of central nervous system diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest rodents with ICH exhibit deficits in the elevated plus maze, sucrose preference, tail suspension, open field, and forced swim tests, 73 , 74 but others have failed 75 resulting in uncertainty whether animal models accurately reflect cognition and depression. 66 Recent studies have investigated genetic links between ICH and depression 76 and the results support the monoaminergic hypothesis, as well as the idea that pro-inflammatory cytokines may stimulate the hypothalamic pituitary adrenal axis. 77 …”
Section: Ich Sequelae and Improving Recoverymentioning
confidence: 78%
“…Although the exact mechanism of ischemic stroke leading to Depression is not clear, a study has found 72 interactive genes and 24 functional pathways that both ischemic stroke and depression are involved in through the analysis of the two. These functions and pathways involve chemokines, cytokines, lipid metabolism, amino acid transport, protein alkylation, protein methylation, etc., and these pathways and genes may be involved in the pathogenesis of post‐stroke depression 24 . Another study found that the mechanism of post‐stroke depression is related to the imbalance of GABA expression, the decrease of GABA can lead to the decrease of noradrenaline, 25 and amino acid neurotransmission dysfunction is one of the pathophysiological mechanisms of depression.…”
Section: Discussionmentioning
confidence: 98%
“…These functions and pathways involve chemokines, cytokines, lipid metabolism, amino acid transport, protein alkylation, protein methylation, etc., and these pathways and genes may be involved in the pathogenesis of post-stroke depression. 24 Another study found that the mechanism of post-stroke depression is related to the imbalance of GABA expression, the decrease of GABA can lead to the decrease of noradrenaline, 25 and amino acid neurotransmission dysfunction is one of the pathophysiological mechanisms of depression. Post-stroke depression is often accompanied by changes in frontal lobe glutamate levels, and the ratio of glutamate/creatinine in the frontal lobe and anterior cingulate gyrus is significantly increased, 26 and glutamate receptor ligands have antidepressant effects.…”
Section: Discussionmentioning
confidence: 99%